Studi Komparatif Berbasis Literatur tentang Strategi Pembelajaran Abad 21 melalui Pendekatan Digital Storytelling dalam Penguatan Pendidikan Karakter - Oktovianti Pratiwi; Cecep Kustandi; Dwi Kusumawardani; Imam Fitri Rahmadi (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
This study aims to explore the role of digital storytelling (DST) as a 21st-century learning strategy in strengthening character education. The rapid development of digital technology and the growing emphasis on student-centered learning have made DST a relevant pedagogical approach that integrates creativity, critical thinking, collaboration, and communication with values-based education. Using a simple systematic literature review (SLR) approach, this study analyzed eight peer-reviewed journal articles published between 2020 and 2024, obtained from international academic databases Scopus. Thematic content analysis was used to synthesize findings and map the contribution of DST to 21st-century learning competencies and character development. The results identified eight key themes: increased student engagement, improved collaboration and communication, enhanced critical thinking and decision-making, creativity and multimodal expression, self-reflection and identity building, empathy and social awareness, interdisciplinary and authentic learning, and the formation of moral values. These findings support constructivist and experiential learning theories and suggest that DST not only enhances cognitive skills but also facilitates affective and ethical development. The study concludes that DST can be a transformative instructional tool in modern education. Practical implications include integrating DST into curricula across disciplines and levels, and equipping educators with training in digital pedagogy and reflective teaching design. Further research is recommended to explore DST implementation in primary and secondary schools and to evaluate its impact using mixed methods.